Socio-economic Stratification and Ill Health in Mexico - Luis Ortiz Hernández; Diana Pérez-Salgado (Social Medicine Publication Group, 2011)
As in other societies, socioeconomic inequality in Mexico is manifested in disparities in morbidity and mortality rates among the Mexican population. Individuals living under the most precarious socio-economic conditions display higher rates of child mortality and other health conditions that are often often associated with poor economic development, such as malnutrition. Moreover, Mexicans from lower socio-economic levels also experience higher rates of weight gain, diabetes mellitus, hypertension, and depression. Individuals with fewer years of education use condoms less frequently, and are also less likely to be tested for HIV; this results in higher HIV infection rates. Social inequality in health is a phenomenon that adversely affects the lower socio-economic populations of Mexico. The reduction and eventual eradication of social inequality in health should be high on the public agenda. Although institutions working in the public health sector can have an impact on reducing health inequalities, fundamental solutions are more likely found within economic, employment, social, and food assistance policies.